PENATAAN RUANG JALAN DI KAWASAN AMPEL DENGAN KONSEP LIVABLE STREET (studi kasus : koridor Jalan Nyamplungan dan Pegirian, Surabaya) - , VINCA YULINTANIA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
These days, it is rare to find any pedestrian ways especially in Indonesia which can give comfort, safe, and also accessible for all pedestrians. The street space function gradually changes into commercial functions. The original function of the street spaces fade away due to the misused of the street. This phenomenon also occured in Ampel district which laid in strategical area and a part of economic commercial area, which has so many traffics problem from the private cars, pedestrians and also street vendors who sells in the pedestrian ways and the streets. Ampel Mosque and Graveyard as the center of Islam culture in Java has been appointed as Religion Tourism Destination by the government. In holidays especially in Ramadhan, many visitors from all around Java come to visit or ziarah to the mosque and graveyard. By then, circulation and activities conflicts between the street users emerged. Based on the livable street concept, the existing of Nyamplungan and Pegirian streets have already shown how both different users and different activities can work in all range of time. The activities occured in the district, but the lack of regulation and its management caused the activities conflict. The research approach use qualitative aspects with rasionalistic method. Begins by identifying the physical existing conditions in the research area and the location of the observation area, added by the facts and problems of the district, which becomes the background of the research. Observation, research and questionaires which is given to the street users, need to be done to support the data. The observation by the researcher, the theory as the base of ideal condition and the users perceptions are the additional data to support the research, and then analyze the data with qualitative method, based on the suitable theories. The results of the research will become the guideline of the street space arrangement. The research result show that the factors which cause the conflicts at the district are the physical setting such as building land use, building setback, and the unsuitable existing pedestrian ways. The non physical setting aspect such as the pedestrian activities, street vendors, on street parking, and loading dock activities. So the arrangement needed at the district to overcome the street space conflicts are the building landuse arrangement, building setback arrangement, and the pedestrian ways, based on the livable street especially for the commercial corridor.